Environmental and economic criteria in early phases of building design through Building Information Modeling: A workflow exploration in developing countries. (December 2022) - Berges-Alvarez, Ileana; Muñoz Sanguinetti, Claudia; Giraldi, Sebastian; Marín-Restrepo, Laura
Abstract: Professionals involved in the early design stages, usually have difficulties understanding the use of Life Cycle Assessment tools. This entails major drawbacks, as it is precisely in these phases when decisions that generate the greatest impacts on the project life cycle are made. As a result, this research aims to propose and test a workflow that integrates environmental and economic sustainability criteria in the early phases of building design using Building Information Modeling and a Chilean database. First, the workflow was conceptualized and implemented. Then, the implementation was validated by a group of professionals from the construction sector, through a practical case. A survey was applied to them to measure the integration in terms of time, applicability, scalability, and ease of understanding. The main findings suggest that the proof of concept is valid and that it could continue to be developed and thus contribute to bringing sustainability criteria into early design stages. Graphical abstract: Image 1 Highlights: Valid proof of concept that helps to bring LCA tools into early design stages. Semi-automated process to make informed decisions in early phases of building design. A link is created between an environmental and economic Chilean database and BIM. A workflow is conceptualized and implemented via Revit, Dynamo, Excel, and PowerBI. Reduced time and flexibility for decision-making without large sustainability expertise.